Asset ownership and foreign-market entry - Horst Raff; Michael Ryan; Frank Stähler (Center for Economic Studies and ifo Institute (CESifo), 2006)
This paper examines the link between a firm's ownership of productive assets and its choice of foreign-market entry strategy. We find that, controlling for industry- and country-specific characteristics, the most productive firms (i.e., those owning the most assets) will enter through greenfield investment, less productive ones will choose M&A, and the least productive ones will export. In addition, the most productive firms are shown to prefer whole ownership to a joint venture. These predictions are confirmed in an econometric analysis of Japanese firm-level data.
Keywords: F15; F12; 330; foreign direct investment; merger and acquisition; joint venture; greenfield investment; firm heterogeneity; productivity; Direktinvestition; Internationale Markteintrittsstrategie; Betriebsvermögen; Produktivität; Schätzung; Theorie; Multinationales Unternehmen; Japan